Peran Kepemimpinan Kepala Sekolah Terhadap Kualitas Kinerja Guru Di SDN Folarora, Kecamatan Tidore, Kota Tidore Kepulauan - Syaban, Novita A.; Dahlan, Fadli; Ruray, Ir Titiek Arafiani (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the role of principal leadership in improving teacher performance at Folarora Elementary School, Tidore Islands City. This study used descriptive qualitative methods, using observation, interviews, and documentation as data collection techniques. The research informants consisted of the principal and homeroom teachers of grades I through VI. The results indicate that the principal plays a significant role in improving educational quality through three main aspects: management, entrepreneurship, and supervision. The principal is able to organize and manage school activities collaboratively, provide guidance and evaluation of teacher performance, and foster an innovative spirit, although its implementation has not been optimal.Teacher performance at Folarora Elementary School is considered good, demonstrated by mastery of four teacher competencies (pedagogical, professional, social, and personality). However, challenges remain, including limited infrastructure and low parental support. Therefore, the principal's leadership has a significant influence on improving teacher performance at Folarora Elementary School.